"I chose teacher education because…": a look into Indonesian future teachers. Issue 1 (2nd January 2021) - Suryani, Anne
ABSTRACT: In Indonesia, implementation of the Law on Teachers and Lecturers in 2005 increased teacher salaries and led to an oversupply of students in teacher education programs, which might be due to no specific teacher education admission criteria. Consequently, limited teaching positions upon graduation result in more teacher education graduates undertaking non-teaching careers. Then, why do students enter teacher education? The study applies the Factors Influencing Teaching Choice (FIT-Choice) theoretical framework. Over eight hundred final-year undergraduate teacher education students from four universities participated in the study. Primary education participants were more motivated by their perceived teaching ability, intrinsic value, job security, time for family, opportunities to have a second job, job transferability, make social contribution, work with children/adolescents, prior teaching and learning experiences, and social influences than all other programs of study. Early childhood and special education participants entered the program because they desire to enhance social equity . English language education participants were the least motivated among others. Improving selection criteria for teacher education admissions, strengthening teacher induction programs, as well as refining the quality of teacher training institutions are crucial to ensure high-quality teachers in Indonesia.